The Long Partition and the Making of Modern South Asia : Refugees, Boundaries, Histories - Zamindar, Vazira Fazila-Yacoobali (Karachi Oxford University Press, 2007)
"In this study based on more than two years of ethnographic and archival research, Vazira Fazila-Yacoobali Zamindar argues that the combined interventions of the two postcolonial states were enormously important in shaping these massive displacements. She examines the long, contentious, and ambivalent process of drawing political boundaries and making distinct nation-states amid this historic chaos."
In particular, Zamindar examines the "Muslim question" at the heart of Partition. From the margins and silences of national histories, she draws out the resistance, bewilderment, and marginalization of north Indian Muslims as they came to be pushed out and divided by both emergent nation-states. It is here that Zamindar asks us to stretch our understanding of "Partition violence" to include this long, and in some sense ongoing, bureaucratic violence of postcolonial nationhood, and to place Partition at the heart of a twentieth century of border-making and nation-state formation.
Include Illustrations, Maps, Tables, Notes, Glossary, Bibliography and Index.
Keywords: Refugees -- Pakistan -- India -- Partition of India (1947) -- Boundaries